Economic proximity and technology flows: South Africa's influence and the role of technological interaction in Botswana's diversification effort - Alexis Habi Yaremye (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2008)
In less than a decade after the end of the apartheid, South Africa has intensified its economic ties with its African neighbours to become one of the top-ten investors and trading partners of many African countries, displacing companies from the former colonial powers in Europe. Among such South Africa's closest trade partners, Botswana has enjoyed one of the highest growth rates in the world for several decades, thanks to its rich mineral reserves, but its diamonds-dominated export structure has barely changed over this growth period. In a national endeavour to reduce its dependence on diamond exports, Botswana recognizes the importance of adopting foreign technologies and deploys sustained efforts to move to high value-added activities in other industries.
Keywords: O19; O32; O33; 330; innovation systems; technological learning; diversification; Technologietransfer; Innovation; Lernprozess; Südafrika; Botsuana